PERAN INOVASI TEKNOLOGI DALAM MENINGKATKAN LITERASI DIGITAL MAHASISWA MENUJU PEMBANGUNAN BERKELANJUTAN - Muhammad Fikri Abdul Malik; Riva Hanafi; Ichsan Fauzia Rachman (JOURNAL SAINS STUDENT RESEARCH, 2024)
Digital literacy is an understanding and skill in using information and communication technology wisely and effectively. With good digital literacy, we can use technology more intelligently and understand the implications of our actions in the digital world. This research aims to discuss further the role of technological innovation in increasing students' digital literacy towards sustainable development using the literature review method. The role of students in increasing digital literacy towards sustainable development is very important. Several aspects that students must have, namely having the skills to use digital devices creatively and innovatively, making maximum use of technology, integrating technology in learning and students are also required to take a role in increasing digital literacy in their immediate environment.